Pengaruh Islamic Human Development Index, Pengangguran, Ketimpangan Pendapatan, dan Upah Minimum Kabupaten Terhadap Kemiskinan (Studi di Provinsi Daerah Istimewa Yogyakarta Periode Tahun 2009-2022) - Anggraini, Natasya (ITB AAS INDONESIA Surakarta, 2024)
This study aims to examine the relationship between the Islamic Human Development Index (IHDI), Unemployment, Income Inequality, and Regency/City Minimum Wage (UMK) to Poverty in Yogyakarta Province in 2009-2022. In this study, I-HDI is calculated using the Simple Weighted Index (SWI) by using a percentage of 20 in 5 dimensions of the index adjusted to the Sharia maqashid indicator. The sample in this study was selected using the saturated sampling method. Based on the saturated sampling method, all members of the population were used as objects in this study. This study uses panel data processed using the Fixed Effect Model regression model. The regression model was used to test the relationship between 4 independent variables, namely I-HDI, Unemployment, Income Inequality, and UMK to the dependent variable, namely poverty. The results of the study show that I-HDI and UMK have a significant negative effect on poverty in Yogyakarta Province in 2009-2022. Meanwhile, the Income Inequality variable did not have a significant effect on poverty in Yogyakarta Province in 2009-2022. Meanwhile, the Unemployment variable has a significant positive effect on poverty in Yogyakarta Province in 2009-2022. However, simultaneously, all independent variables studied had an effect on poverty in Yogyakarta Province in 2009-2022.